2016
DOI: 10.1097/j.pain.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of pain, personality, and brain plasticity following peripheral nerve injury

Abstract: We do not know precisely why pain develops and becomes chronic after peripheral nerve injury (PNI), but it is likely due to biological and psychological factors. Here, we tested the hypotheses that (1) high Pain Catastrophizing Scale (PCS) scores at the time of injury and repair are associated with pain and cold sensitivity after 1-year recovery and (2) insula gray matter changes reflect the course of injury and improvements over time. Ten patients with complete median and/or ulnar nerve transections and surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 76 publications
0
12
0
2
Order By: Relevance
“…An important question still lingering in the field is whether brain abnormalities specific to a pain condition renormalize after a treatment, and whether this renormalization is linked to significant analgesia. Several studies have shown reversibility in structural or functional properties for various treatment approaches and pain conditions (Cummiford et al, 2016;Goswami, Anastakis, Katz, & Davis, 2016;Gwilym et al, 2010;Seminowicz et al, 2011Seminowicz et al, , 2013. However, none of them has investigated unbiased whole brain structural and resting state functional reorganization in relation with original difference with controls.…”
Section: Discussionmentioning
confidence: 99%
“…An important question still lingering in the field is whether brain abnormalities specific to a pain condition renormalize after a treatment, and whether this renormalization is linked to significant analgesia. Several studies have shown reversibility in structural or functional properties for various treatment approaches and pain conditions (Cummiford et al, 2016;Goswami, Anastakis, Katz, & Davis, 2016;Gwilym et al, 2010;Seminowicz et al, 2011Seminowicz et al, , 2013. However, none of them has investigated unbiased whole brain structural and resting state functional reorganization in relation with original difference with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the brain imaging studies of PHN were conducted using fMRI, we should notice that mounting evidence indicated that NP resulted in or was accompanied by plastic change or structural abnormality in human (65)(66)(67)(68)(69) and murine (70,71) brains. Much of the plastic and structural alterations took place in pain-processing regions.…”
Section: E311mentioning
confidence: 99%
“…Aynı zamanda periferik sinir hasarı sonrası hastalarda kronik ağrı, kişilik değişikliği ve uyum sorunu gibi gündelik yaşama yansıyan sendromlar gelişmektedir. Bu durum hem hastada hem de çevresinde duygu bozukluğuna neden olmak da psikolojik sorunları da beraberinde getirmektedir (4) . Olgumuzda ve ailesinde de antidepresan ilaç kullanım öyküsü mevcuttu.…”
Section: Discussionunclassified
“…Postoperatif medikal tedavide öncelikle gabapentin, pregabalin, alfa-lipoik asit nöropatik ağrıyı engelleyip ve sinir rejenerasyonunu artırdığı için önerilmektedir (3,4,6) . İmmün supresif ilaçların ise bu tedavi modalitesinde yeri tartışmalıdır (2,5) .…”
Section: Resim 3 Peroneal Sinirin Allogreft Ile Tamiri Sonrası Görünunclassified